The Impact of Disciplining Students on Their Performance in Secondary Schools in Kabale Municipality Kabale District. - Twinomugisha, Innocent (Kabale University, 2024)
The study examined the impact of disciplining students on their performance in secondary school students in Kabale Municipality Kabale district. The objectives of the study were, to identify the effect of disciplining students on the performance of selected secondary school students, to examine the impacts of indiscipline on students in secondary school students, and to assess the possible solutions for indiscipline among students in selected secondary school students. The study used a descriptive research design and data was collected using interviews and questionnaires. The study impacts of disciplining students on their performance selected secondary school students, the highest number of the respondents mentioned that indiscipline leads to poor performance in schools while the least number of the respondents mentioned that it leads to accidents. Other respondents mentioned that students may be, expelled from school, or delayed in completion of the syllabus, The study results on the impacts of disciplining students on their performance in selected secondary school students in inKabale municipality Kabale district, the highest number of respondents mentioned that teachers tend to be role models to the learners, the lowest number of respondents mentioned that teachers are expected to have specific objectives which help them to choose a relevant content and that the teacher helps to identify appropriate teaching and learning resources, other respondents mentioned that they also contribute to the building of better characters among the students, that teachers help in the importation of knowledge to students and that they help to select suitable methods to help achieve the objectives and determine areas and methods of assessments. The study results on methods of teaching used to enhance moral development in selected secondary school students in Kabale Municipality, Kabale district, the highest number of respondents mentioned the use of instructional methods, the lowest number of respondents talked of exchanging ideas, other respondents mentioned group planning activities, use of films, video and taped audios presentations and storytelling. The study recommended that educators especially district officials should make visits to the schools to ensure that teachers they should also ensure that teachers use the recommended resources of teaching rather than the commercial revision materials aimed at passing examinations.